2016
DOI: 10.1123/jpah.2015-0593
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climatic Conditions on Physical Activity: A 2-Year Cohort Study in the Arabian Gulf Region

Abstract: Increased temperature and humidity are associated with a reduction in the number of steps taken per day. Community-based PA programs in hot hot/humid climates should consider novel approaches to increase PA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Finally, Al-Mohannadi et al [52] led a 2-year cohort study in a sample of 2,088 Qatar residents (Arabian Gulf region). The study assessed associations between 2-year changes in objectively assessed physical activity (i.e., step counts per day and aerobic steps per day) and climatic conditions (i.e., outdoor average temperature, humidity, cloud cover, rain/thunderstorms and WetBulb Globe Temperature, WBGT).…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Finally, Al-Mohannadi et al [52] led a 2-year cohort study in a sample of 2,088 Qatar residents (Arabian Gulf region). The study assessed associations between 2-year changes in objectively assessed physical activity (i.e., step counts per day and aerobic steps per day) and climatic conditions (i.e., outdoor average temperature, humidity, cloud cover, rain/thunderstorms and WetBulb Globe Temperature, WBGT).…”
Section: Empirical Studiesmentioning
confidence: 99%
“…These studies considered daily weather variables for temperature, rainfall, relative humidity, wind speed, sea level pressure, snow on ground etc. along with demographic variables [ 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…The other studies found using multilevel models that the effect of temperature and humidity were both significant positive determinants of step counts while rainfall, snow depth and wind speed had a significant negative relationship with daily step counts [ 72 , 73 ]. A significant interaction effect for maximum wind speed and BMI was also found, with maximum wind speed having more of an effect on individuals with lower (BMI = 20) and higher BMI’s (BMI = 35) [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Qatar, hot weather is a major barrier to physical activity and impacts the average number of steps adults take per day: as heat and humidity increase, the number of daily steps decreases (Al-Mohannadi, Farooq, & Burnett, 2016). Promoting physical activity in indoor air-conditioned areas in a workplace can provide an alternative environment where workers could meet daily physical activity needs.…”
Section: Discussionmentioning
confidence: 99%